Towards developing experience based factory model for software requirement engineering process in collaborative environment - Hanafiah, Mastura; Abdullah, Rusli (2014)
Requirement engineering is a crucial process in software development. It is known that requirement related activities are repetitive, time-consuming and requires a lot of human involvement. Furthermore, inadequate requirement management and inappropriate requirement engineering process are among the common issues in requirement engineering. Knowledge and experiences in requirement engineering should be managed systematically and efficiently for the purpose of sharing and reuse. This paper discusses the proposal for the development of experience based factory model for requirement engineering process in collaborative environment. The proposed model, namely Requirement Engineering for Experience Based Factory Model (RE-EBF-Model), has the objective to manage requirement knowledge effectively to maximize the benefit of knowledge sharing among the community of practice. A comprehensive study of literature review and experts’ opinion from a preliminary survey serve as the guideline for the model development.